Para vaginal dermoid cyst: a rare occurrence - Bhatia, Ruby; Mohi, Manjit Kaur; Gupta, Anju; Goyal, Sonia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Dermoid cyst (cystic teratoma) showing well differentiated derivatives of all three germs cell layers, is a benign germ cell tumour. Ovaries remain the commonest site. Paravaginal dermoid cyst is a rare occurrence. Pre-operative diagnosis is usually difficult in majority of cases. They constitute less than 4% of all extragonadal teratomas. A 28-year old, P2L2 female presented with paravaginal cyst, 10×10cms, non-tender, soft swelling, cystic in consistency occupying posterior and left part of rectovaginal septum. Trans vaginal excision of cyst under regional anaesthesia done. Cyst was ruptured while excision showing putty material with tuft of hairs. A retrospective diagnosis of mature teratoma/paravaginal dermoid cyst was made on histopathological examination. Paravaginal dermoid cyst, a benign cystic teratoma is a very rare occurrence. Transvaginal excision of dermoid cyst under anaesthesia remains treatment of choice. Retrospective diagnosis on histopathological examination remains confirmatory as it may be missed on sonography if teeth are not present in dermoid cyst.